An Analysis of The English-Indonesian Translation Methods in Olivia “Guts” Album Translated by Youtube Indolirik Account - Sabta Togarma Sitinjak; Rotua Elfrida Pangaribuan; Erika Sinambela (Journal of Language Education (JoLE), 2025)
This study contains an analysis of translation method in Guts album by Olivia Rodrigo translated Indolirik. The writer used theory of translation method based on Newmark theory. They were wordfor-word translation, literal translation, faithful translation, semantic translation, adaption, free translation, idiomatic translation, communicative translation.This study used qualitative descriptive method in analyzing the data. Problem discussed in this research were 1) what types of translation methods are found in Guts album? 2)What is the most dominant type of translation method found in the Guts album? Finally, the researcher found the translation method that is used by translator of song lyric in “Guts” album they are word-for-word translation method for 2 data with frequency of 0.78%, literal translation method as many as 69 data with frequency of 26.74%, faithful translation method as many as 107 data with frequency of 41.47%, semantic translation method as many as 58 data with frequency of 22,48%, adaptation translation method as many as 9 data with frequency of 3,49%, free translation method as many as 8 data with frequency of 3,10%, idiomatic translation method as many as 2 data with frequency of 0,78% and communicative translation method as many as 3 data with frequency of 1,16%. It shows that the most dominant method which is used by the translator is faithful translation that there are 107 or 41.47%.